Yin Yang 1 Dynamically Regulates Antiviral Innate Immune Responses During Viral Infection - Jie Zan; Hao Zhang; Ai-Ping Gu; Kai-Lun Zhong; Min-Yi Lu; Xiao-Xin Bai; Jin-Yang Zhang; Jun Cai (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Type I interferon (IFN-1) production and IFN-1 signaling play critical roles in the host antiviral innate immune responses. Although transcription factor Yin Yang 1 (YY1) has been reported to have a dual activator/repressor role during the regulation of interferon beta (IFN-β) promoter activity, the roles of YY1 in the regulation of upstream signaling pathways leading to IFN-1 induction and IFN-1 signaling during viral infection remain to be elucidated. Methods: The roles of YY1 in IFN-1 production and IFN-1 signaling were investigated using immunoblotting, real-time PCR, small interfering RNA (siRNA)-mediated YY1 knockdown, YY1 overexpression by transient transfection, and co-immunoprecipitation, using mouse cells. Results: YY1 was shown to interact with STAT1 in the absence of viral infection. Following viral infection, YY1 protein expression levels were decreased. YY1 knockdown led to a considerable downregulation of phosphorylated (p) TBK1 and pIRF3 expressions, while YY1 overexpression significantly upregulated pTBK1 and pIRF3 expression levels and promoted virus-induced IFN-β production. Additionally, YY1 knockdown led to a significant upregulation of pSTAT1, pSTAT2 and antiviral interferon-stimulated genes, and inhibited viral replication. Conclusion: We demonstrated here that YY1 interacts with STAT1 and dynamically regulates the induction of IFN-1 production and activation of IFN-1 signaling in different stages during viral infection.